Mapping the relationship between perceived involution and subjective well-being in Chinese university students: a network analysis across gender and grade levels - Li, Chen (Frontiers in Psychology, 2025)
Involution, as a rising sociocultural phenomenon in contemporary Chinese society, has raised concerns about its potential psychological impact on young people. However, little is known about how perceived involution relates to university students’ well-being and whether such patterns differ by gender and academic stage. The present study investigated perceived involution and subjective well-being among 5,235 university students using network analysis. Distinct characteristics of involution perception were identified across gender and academic year. Network structures revealed largely negative associations between perceived involution and well-being, with female students displaying denser and more interconnected networks than males. Additionally, comparisons across grade levels indicated differentiated psychological profiles: lower-grade students were more affected by academic stress, while upper-grade students showed stronger links between competitive norms and future-related concerns. These findings contribute to a nuanced understanding of how involution manifests psychologically and underscore the value of network analysis in mapping complex relationships between cultural stressors and mental health in youth populations.